2018
DOI: 10.1038/s41593-018-0229-7
|View full text |Cite
|
Sign up to set email alerts
|

Social reward monitoring and valuation in the macaque brain

Abstract: Behaviors are influenced by rewards to both oneself and others, but the neurons and neural connections that monitor and evaluate rewards in social contexts are unknown. To address this issue, we devised a social Pavlovian conditioning procedure for pairs of monkeys. Despite being constant in amount and probability, the subjective value of forthcoming self-rewards, as indexed by licking and choice behaviors, decreased as partner-reward probability increased. This value modulation was absent when the conspecific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
84
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(96 citation statements)
references
References 45 publications
10
84
2
Order By: Relevance
“…This finding indicates that the value of one's own reward is subjectively lowered by a higher incidence of rewards to conspecifics. Note that, in our behavioral procedure, the order of outcome revelation and the context of resource limitation were both critical factors for the emergence of subjective value modulation, as reported previously (18).…”
Section: Significancesupporting
confidence: 57%
See 3 more Smart Citations
“…This finding indicates that the value of one's own reward is subjectively lowered by a higher incidence of rewards to conspecifics. Note that, in our behavioral procedure, the order of outcome revelation and the context of resource limitation were both critical factors for the emergence of subjective value modulation, as reported previously (18).…”
Section: Significancesupporting
confidence: 57%
“…What might be the impact of partner's reward contexts on LH activity? We previously reported that subjective value modulation, as indexed by the licking movement, was absent in the M2variable block when the partner monkey was replaced with a water-collecting bottle (18). We also reported that the subjective value modulation, as indexed by the licking and choice behaviors, was significantly attenuated or absent in the M2-variable block when the partner monkey was present in front of M1 but was deprived of access to a reward (18).…”
Section: Significancementioning
confidence: 90%
See 2 more Smart Citations
“…In this behavioral paradigm, neurons in the rostral anterior cingulate gyrus (ACCg) code the chosen social outcome 7 and neurons in the amygdala code the value of juice amount similarly regardless of whether it is delivered to the self or the other monkey, but not when it is delivered to a jar in the nonsocial control condition 8 . In a similar paradigm, researchers found neurons in the dorsal convexity of the medial prefrontal cortex that selectively coded reward for either the actor monkey or a partner monkey 9 .…”
Section: Introductionmentioning
confidence: 99%